Basal Cell Carcinoma of the External Genitalia: A Population-Based Analysis - Chen, Xi; Hou, Yulong; Chen, Can; Jiang, Guan (Frontiers in Oncology, 2021)
Abstract Basal cell carcinoma (BCC) located on the genitalia is rare; data on the clinicopathologic features and survival outcomes are only available through case reports and small case series studies. Purpose: This study aimed to explore the epidemiology and identify the prognostic factors of genital BCCs. Methods: We queried the 18 registries of the Surveillance, Epidemiology, and End Results database for patients with primary BCCs of the genital skin from 2000 through 2017. The primary endpoint was overall survival (OS) and disease specific survival (DSS). Kaplan-Meier survival analysis was conducted to assess the impact of clinicopathological variables on OS and DSS. Multivariate Cox proportional hazards model was performed to evaluate risk factors for OS. Results: A total of 1607 cases of genital BCCs were identified. The cohort was composed of 1352 women (84.1%) and 255 men (15.9%). The median (P25, P75) age of the entire cohort was 73（63- 82）years. White patients accounted for 87.2% of the cases. For women and men, the most common site of involvement was the labia majora (89.6%) and scrotum (74.5%), respectively. The majority of patients with genital BCC had localized disease (75.5%). Kaplan-Meier survival analysis showed that female genital BCCs experienced better DSS than men (209.1 months vs 194.8 months); for men, BCCs located on the scrotum had better DSS and OS than those on the penis (P < 0.05 for both endpoints). All patients with distant disease died of disease-specific death, and the average survival time was 8.2 months. Multivariate analysis revealed that age, primary site, and stage were independent determinants of OS for men, while tumor size, histologic subtype, and race were not. For women, factors associated with worse OS included increasing age, tumor size more than 2 cm, and distant disease; factors associated with a decreased risk included “other” and “unknown” races. Conclusion: The prognosis of genital BCCs is excellent, while the survival of distant disease is very poor. Despite similar clinicopathologic features and overall survival outcomes, men and women should be treated as two different entities when making survival predictions.